Modelling of terrestrial and underwater biotopes of Galindez Island (Argentine Islands, West Antarctica) using a geographic information system - A. Yu. Utevsky; O. I. Sinna; A. Y. Berezkina; D. V. Shmyrov; V. S. Popov (Ukrainian Antarctic Journal, 2016)
Geographic information systems (GIS) are a modern tool for the collection, storage, analysis and graphical visualization of spatial data and related information. The results of unification into a single GIS resource of the acoustic survey of selected areas of the bottom floor, biodiversity analysis of underwater landscapes and chemical and morphological analyses of primitive soils of Galindez Island (Argentine Islands, West Antarctica) are presented. Standard cartographic mapping and three-dimensional modeling using ArcGISTM are used to visualize the data.